2015
DOI: 10.15761/imm.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Nasal hygiene in patients with end-stage renal disease

Abstract: Staphylococcus aureus is the most common endogenous infection in patients with end-stage renal disease (ESRD), and the anterior nares are the most common endogenous S. aureus carrier sites. Eliminating nasal S. aureus will greatly benefit ESRD patients. However, prophylactic topical nasal usage of mupirocin or any kind of antibiotic is against the principles of antibiotic usage. Nasal irrigation has been demonstrated to significantly increase ciliary clearance and decrease mucous inflammation, and has been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Recent studies have indicated a potential connection between CKD and sinonasal conditions, such as epistaxis, infections, and olfactory dysfunction [ 13 , 14 , 15 ]. However, only a few studies have assessed the direct association between CKD and CRS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated a potential connection between CKD and sinonasal conditions, such as epistaxis, infections, and olfactory dysfunction [ 13 , 14 , 15 ]. However, only a few studies have assessed the direct association between CKD and CRS.…”
Section: Introductionmentioning
confidence: 99%